2017
DOI: 10.1111/apt.14144
|View full text |Cite
|
Sign up to set email alerts
|

Review article: recent insights into clinical decision‐making in severe alcoholic hepatitis

Abstract: Recent studies have helped to define patients who may benefit from corticosteroid treatment. However, there remains a need for more accurate scores of prognosis and treatment response, and a clear need for alternative treatments for those patients not responding to corticosteroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…It uses age, serum bilirubin, blood urea nitrogen, PT ratio and the peripheral white cell count as variables, with a score of <9 being associated with an extremely poor mortality [33]. Research has shown that GAHS ≥ 9 may benefit from corticosteroid treatment, whereas those with a GAHS < 9 are unlikely to benefit from such treatment even if the DF is ≥32 [34,35]. One report suggests that ABIC, GAHS and MELD could be superior to the DF score [33].…”
Section: Glasgow Alcoholic Hepatitis Score (Gahs)mentioning
confidence: 99%
“…It uses age, serum bilirubin, blood urea nitrogen, PT ratio and the peripheral white cell count as variables, with a score of <9 being associated with an extremely poor mortality [33]. Research has shown that GAHS ≥ 9 may benefit from corticosteroid treatment, whereas those with a GAHS < 9 are unlikely to benefit from such treatment even if the DF is ≥32 [34,35]. One report suggests that ABIC, GAHS and MELD could be superior to the DF score [33].…”
Section: Glasgow Alcoholic Hepatitis Score (Gahs)mentioning
confidence: 99%